Effect of pulmonary vein anatomy and pulmonary vein diameters on outcome of cryoballoon catheter ablation for atrial fibrillation - Güler, Ekrem; Babür Güler, Gamze; Demir, Gültekin Günhan; Kızılırmak, Filiz; Güneş, Hacı Murat; Barutçu, İrfan; Kılıçaslan, Fethi (Wiley, 2015)
BackgroundIn this study, we aimed to determine pulmonary vein (PV) variation patterns in patients undergoing cryoballoon ablation for atrial fibrillation (AF) and their impacts on procedural success and recurrence and also to identify predictors for recurrence. MethodsWe enrolled 54 patients with AF and having symptoms despite medical therapy. Prior to the procedure, PV variation and left atrium (LA) size were evaluated in all patients by computed tomography scan. Ablation procedure was performed with single balloon and predictors for AF recurrence were determined. ResultsThe study population consisted of 54 patients (male: 50 [27%], mean age: 53 12) with AF. Paroxysmal AF and persistent AF were detected in 55.6% (30) and 44.4% (24) of the patients, respectively. Mean procedural and fluoroscopy times were 73 +/- 19 minutes and 16 +/- 4 minutes, respectively. The number of the patients with PV variation of right pulmonary vein (RPV) with >2 ostia and accessory PV was 27.8% (15) and 18.5% (10). During the follow-up, 20.4% (11) of patients had AF recurrence. Patients with recurrence had greater transverse LA size (62 +/- 6 mm vs 57 +/- 5 mm, P: 0014), longitudinal LA size (65 +/- 5 mm vs 61 +/- 6 mm, P: 0025), LA volume (78 +/- 17 mL vs 65 +/- 14 mL, P: 0011), fluoroscopy time (20.4 +/- 4.6 minutes vs 15.7 +/- 3.5 minutes, P: 0001), RPV with >2 ostia (72.7% vs 27.3%, P: 0001), right upper pulmonary vein (RUPV) diameter (21.6 +/- 2.8 cm vs 15.8 +/- 2.1 cm; P < 0001), and persistent AF (33.3% vs 66.7%, P: 0046). In multivariate analysis, RUPV diameter (: 1006; P: 0010; odds ratio [OR]: 2736; 95% confidence interval [CI]: [1267-5906]) and fluoroscopy time (: 0327; P: 0050; OR: 1386; 95% CI: [1000-1921]) were determined as independent predictors for AF recurrence. ConclusionsTransverse and longitudinal LA size, LA volume, fluoroscopy time, presence of persistent AF, RUPV size, and the number of RPV ostia are associated with AF recurrence following cryoballoon-based ablation. RUPV size and fluoroscopy time are predictors for recurrence.
WOS: 000358697100011
PubMed ID: 25974075
Keywords: Atrial Fibrillation; Pulmonary Vein Isolation; Pulmonary Vein Variation; Cryoballoon; Recurrence